2018
DOI: 10.1164/rccm.201709-1893oc
|View full text |Cite
|
Sign up to set email alerts
|

Does Extracorporeal Membrane Oxygenation Improve Survival in Pediatric Acute Respiratory Failure?

Abstract: In children with severe ARDS, our results do not demonstrate that ECMO-supported children have superior outcomes compared with non-ECMO-supported children. Definitive answers will require a rigorous multisite randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 56 publications
2
45
1
2
Order By: Relevance
“…This data has particular value in conversations with patients and caregivers, and can be used to convey prognostication and set expectations for survival in both the short-and long-term, given the existing data. Overall mortality rates were higher among patients with respiratory failure, which is contrary to what has been seen previously [8][9][10]. Although the reason for this remains unclear, it may reflect the selective use of ECMO at the included centers, as compared to other centers in the ELSO database.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This data has particular value in conversations with patients and caregivers, and can be used to convey prognostication and set expectations for survival in both the short-and long-term, given the existing data. Overall mortality rates were higher among patients with respiratory failure, which is contrary to what has been seen previously [8][9][10]. Although the reason for this remains unclear, it may reflect the selective use of ECMO at the included centers, as compared to other centers in the ELSO database.…”
Section: Discussioncontrasting
confidence: 76%
“…Across the world, ECMO utilization was historically more common among neonates than older children; however, this trend has changed over the last decade with an increase in pediatric cardiac and pediatric respiratory utilization [9]. For patients with respiratory failure, in-hospital mortality among those receiving ECMO (largely venovenous [VV-ECMO]) was approximately 25% and did not differ from propensity-matched controls [10]. However, in the pediatric population, venoarterial ECMO (VA-ECMO) is more common.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no RCT examining the effect of ECMO on outcome in pediatric sepsis has been published. In the absence of such data, using propensity score matching, Barbaro et al [481] reported that children with severe PARDS enrolled in the RESTORE trial had similar mortality rates when supported with ECMO (15/61, 25%) as compared with those who were not (18/61, 30%) [482] (Supplemental Table 33, Supplemental Digital Content 1, http://links .lww.com/PCC/B139). Research is underway to determine optimal pre-ECMO candidacy [483] as measures of renal, hepatic, neurologic, and hematologic dysfunction, and particularly the presence of bloodstream infections, seem to discriminate mortality risk better than traditional pediatric severity of illness scores such as PRISM, Pediatric Index of Mortality, and Pediatric Logistic Organ S47 Dysfunction.…”
Section: We Suggest Using Venovenous Ecmo In Children With Sepsis-indmentioning
confidence: 99%
“…In adults with very severe acute respiratory distress syndrome (ARDS), the ECMO for Severe ARDS (EOLIA) trial was stopped early for a predicted lack of a significant difference in the primary outcome of mortality at 60 days between the ECMO and the continued conventional treatment arms ( 17 ). A similar trial has not been conducted in children, however recent results from a secondary analysis of the Randomized Evaluation of Sedation Titration for Respiratory Failure (RESTORE) trial suggest that a trial of ECMO vs. continued conventional management for severe pediatric ARDS may be justified ( 18 ). The authors' conclusion was based on lack of differences in patient outcomes comparing RESTORE study participants managed with ECMO vs. matched controls managed with conventional mechanical ventilation, along with the finding of wide variability in clinical practice with regards to mechanical ventilation strategies and determination of ECMO candidacy and timing for ECMO cannulation that confirmed previously published survey data ( 18 , 19 ).…”
Section: Clinical Research Studies In Critically Ill Children On Ecmomentioning
confidence: 99%